Endoscopic Tunnel Dissection of an Oesophageal Bronchogenic Cyst: A Case Report - Yiu, Sharon Wing-Kee; Yozu, Masato; Luo, Derek; Sekra, Anurag (The International Journal of Gastroenterology and Hepatology Diseases, 2024)
IntroductionA bronchogenic cyst is a very rare congenital malformation typically found in the middle and superior mediastinum. Infrequently, it can be located in the pericardium, diaphragm, oesophagus, and stomach. Intramural oesophageal bronchogenic cysts are highly uncommon, and because of this, they have not been extensively studied. They are generally asymptomatic; however, due to their potential to cause complications, such as evolution into malignancy, the removal of these cysts is recommended. Routinely, techniques, including thoracotomy and thoracoscopy, have been adopted for excision. This case report details our success in performing a complete resection of an intramural oesophageal bronchogenic cyst via a novel approach of Submucosal Tunneling Endoscopic Resection (STER).Case PresentationA 62-year-old woman was referred for an outpatient gastroscopy and colonoscopy for further investigation of her unexplained iron deficiency anaemia, abdominal pain, diarrhoea, and weight loss. A single oesophageal nodule was found on gastroscopy, which was further characterized and deemed to be benign on upper endoscopic ultrasound. The lesion was removed via the STER technique. During the procedure, submucosal fibres were dissected and a full-thickness myotomy was performed to completely remove the lesion. Histologically, the lesion showed a cyst lining comprising ciliated columnar epithelium, a finding consistent with a bronchogenic cyst. The patient maintained a normal diet and remained asymptomatic throughout the follow-up period.ConclusionThis report documents the successful resection of an oesophageal bronchogenic cyst via the STER technique. This novel approach appears to be a valuable tool with negligible invasiveness. It provides a feasible option for patients.
Keywords: Submucosal Tunnelling Endoscopic Resection (STER)